Desafios da formação docente no curso de pedagogia: Aligeiramento e Pragmatismo - Cação, Maria Izaura [UNESP] (My University, 2013)
This paper analyzes recent policies of teacher eduation in Brazil related to the employment and professional dimmensions of the teaching career. It analyzes teacher education policies, and the guidelines established by the World Bank in the 1990s, to reform higher education in the so-called developing countries, focusing on th implementation of neolibera educational policies. These policies have produced a new value for educational insititutions: they are emptying schools of education; defertilization of schools; deintellectualization of the teacher profession; pauperization, fragmentation and emptying the contents teacher education programs and recontextualization of the nexus theory-practice. The reforms after the Directives and Bases of Education - Law No. 9394/1996, with respect to the education of teachers, are analyzed in relation to the process of productive restructuring. We analyze the relation between theory and practice, given the National Curriculum Guidelines for the Education Course (DCNCP, 2006), focusing on the Course of Pedagogy for the Faculty of Philosophy and Science, at the Paulista State University, Campus of Marilia. This course offers an extensive practical training, but restricted as to the academic content offered, limiting the possibilities of an in-depth training for the future teachers. Discussing these relations, this article presents the assessment of the students in the course and concludes offering perspectives for a humanizing and critical training.
Teacher education challenges for schools of education: Pragmatism and simplification
Keywords: Educational reforms; Humanizing praxis; Pedagogy course; Teacher training; Theory-practice relationship